MODERASI KEYAKINAN HUKUM KARMA DAN MORALITAS PADA HUBUNGAN WHISTLEBLOWING DAN PENCEGAHAN KECURANGAN - Yuniasih, Ni Wayan; Sudiana, I Wayan; Putra, I Putu Deddy Samtika (Buletin Studi Ekonomi, 2022)
Various research results indicate that the implementation of whistleblowing in fraud prevention is influenced by other factors. This study purpose to test the effectiveness of the whistleblowing and examine the spiritual and moral factors that may affect its effectiveness. This research was conducted at 34 People's Credit Institutions in Denpasar City. Research respondents totaled 84 people who were determined by probability sampling technique. The research variables were measured by the indicators contained in the statement of the questionnaire. Data analysis was performed using moderated regression analysis. The results showed that whistleblowing had a positive effect on fraud prevention. The belief in the law of karma phala is able to moderate the whistleblowing relationship and prevent fraud. Individuals who believe in the law of karma phala will use the whistleblowing system to assist organizations in preventing fraud. Individual morality is also able to moderate the whistleblowing relationship and fraud prevention.